College Major Choice and Ability: Why is General Ability not Enough? - Tjaša Loga; Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
The choice of college major is one of the most important decisions students make. In this paper we study the impact of ability on college major choice,using a data set for full-time students enrolled in four-year business and economics programs offered by the Faculty of Economics, University of Ljubljana. We distinguish between general and major-specific ability, which measure different dimensions of cognitive ability. We show that both measures are important in explaining individual decisions and that misleading results can follow from observing only commonly employed general ability. We also find important gender differences as males are more likely to base their major choice on the ability to complete coursework, while females are more likely to decide according to unobserved preferences.
Keywords: I23; 330; College Majors; Ability; Gender Differences; Studienfach; Berufswahl; Intelligenz; Geschlecht; Slowenien; Ljubljana